Pengaruh Disiplin Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan PT Pandu Siwi Sentosa - Rusdiani, Nina; Ekawaty, Novian (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research was conducted to describe, test, and analyze the influence of work discipline and job satisfaction on the performance of PT Pandu Siwi Sentosa employees in East Jakarta. In this research, the method used is a quantitative method with descriptive and verification analysis. The verification analysis used is a multiple regression analysis. The results of the verification analysis found that there was a partial influence between Work Discipline and Job Satisfaction on Employee Performance of 0.493 and 0.424 respectively. Which means that work discipline has an influence on employee performance of 0.493, while job satisfaction is 0.424. Meanwhile, the results of the simultaneous test showed that the variables of work discipline and job satisfaction together had an influence on employee performance of 0.261. This means that work discipline and job satisfaction have an influence of 0.261, and the remaining 0.739 is influenced by other variables outside the research.